Competitiveness and Trade Flows of Indonesian Processed Tuna in The International Market - Khoirul Ichsan; Nia Rosiana; Rita Nurmalina (Faculty of Animal and Agricultural Science, Diponegoro University, 2026)
Indonesia is one of the biggest producers of tuna with 19.1% of the world's supply. However, despite steadily rising demand worldwide, its exports of processed tuna have decreased. This study examines the competitiveness of Indonesian processed tuna and the factors influencing its export performance across major destination markets during the period 2012–2023 by integrating the Revealed Comparative Advantage (RCA) index with an import demand model estimated using panel data regression under the Random Effect Model (REM). The results show that Indonesian processed tuna is highly competitive in many destination markets, with RCA values higher than 4 in nine out of ten nations. However, competitiveness Spain is still comparatively low because Spain serves as a processing and re-export hub. The empirical results show that while geographic distance and exchange rates have significant negative effects on Indonesia's processed tuna export volume, real GDP per capita in destination countries has a positive and statistically significant effect. Import tariffs and non-tariff measures like Technical Barriers to Trade (TBT) and Sanitary and Phytosanitary (SPS) measures have no statistically significant effects. To determine how to strengthen Indonesia's position in the global processed tuna trade, this study links destination-specific competitiveness with export performance and offers policy-relevant insights that highlight the significance of focusing on high-income consumption-oriented markets, improving logistics efficiency, and maintaining exchange rate competitiveness.